The SmartAG Partner: CCAFS East Africa Quarterly Newsletter, July - September 2017 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
We are pleased to share with you our SmartAg Partner newsletter, highlighting policy engagement and ongoing research in the third quarter of 2017. In July, we hosted an online discussion forum on ‘Engaging African Youth in Agribusiness in a Changing Climate,’ a platform that created space to discuss critical issues facing African youths. The online discussion —which attracted 79 comments — ran for one month to commemorate World Youth Skills Day (15 July) and International Youth Day (12 August) and culminated in a webinar attended by 80 participants on 30 August. Climate services play a key role in supporting the resilience of communities. The Rwanda Climate Services for Agriculture project organized a four-day training of trainers on Participatory Integrated Climate Services for Agriculture (PICSA) in Huye district. This was followed by a field training process allowed participants to work with smallholder farmers on the PICSA process. Additionally, to empower decision-makers on climate services, IGAD Climate Prediction & Applications Centre (ICPAC) organized a workshop on ‘ Existing and New Tools for Drought Monitoring and Forecasting in Eastern Africa’. A recently published journal on ‘Adoption and Dissemination Pathways for Climate-Smart Agriculture Technologies and Practices for Climate-Resilient Livelihoods in Lushoto, Northeast Tanzania’ assesses farmer adoption of climate-smart agricultural practices and innovation after being exposed to Farms of the Future Approach (FotF).